The Transformation of Financial Literacy in the Digital Era: a Systematic Literature Review on Concepts, Dimensions, and Future Research Directions - Agatha Helena Deze (International Journal of Economics, Commerce, and Management, 2026)
The rapid growth of digital financial technologies has transformed how individuals access and manage financial resources, yet disparities in financial literacy remain a critical issue. This study aims to systematically examine the transformation of financial literacy in the digital era by identifying its conceptual development, key dimensions, and future research directions. A qualitative approach using the Systematic Literature Review (SLR) method was employed, following a structured process of article selection, screening, and synthesis from reputable academic databases. The findings reveal that financial literacy has evolved into a multidimensional construct encompassing financial knowledge, behavior, attitudes, and digital financial literacy. The study also highlights that technological advancement increases both opportunities and risks, requiring individuals to possess higher levels of cognitive and digital competence. Furthermore, the results indicate the need for more integrative frameworks and inclusive research across diverse contexts. This research contributes by offering a comprehensive conceptual mapping and identifying research gaps to guide future studies in the field of digital financial literacy.